Clinical characteristics and molecular detection of bordetella pertussis in hospitalized children with a clinical diagnosis of whooping cough in Peru - Del Valle-Mendoza, Juana (2021)
Background and Objectives: Pertussis is an infectious disease caused by the Gram-negative bacterium Bordetella pertussis. In Peru, actual public health programs indicate that vaccination against B. pertussis must be mandatory and generalized, be-sides all detected cases must be reported. The objective of this study was to determine the prevalence of B. pertussis among children under five years of age with a presumptive diagnosis of whopping cough in Cajamarca, a region located in northern Peru. Materials and Methods: The population of this cross-sectional study were children under 5 years old hospitalized as presumptive cases of pertussis during December 2017 to December 2018. The nasopharyngeal samples were analyzed by real-time PCR for the detection of B. pertussis. Results: B. pertussis was identified as PCR + in 42.3% of our sample (33/78). The clinical presentation that was observed most frequently includes paroxysmal coughing (97%), difficulty breathing (69.7%), cyanosis (72.7%) and post-tussive em-esis (60.6%). Additionally, pneumonia was the most observed complication (33.3%). Four of the patients with PCR+ for B. pertussis presented only lymphocytosis, five only leukocytosis, two patients with decreased leukocytosis and lymphocytes and only one patient with leukopenia and relative lymphocytosis. There was a percentage of 84.8% of unvaccinated children in the PCR+ group. Finally, the mother was the most frequent symptom carrier (18.2%). Conclusion: In conclusion, in the studied population there is a high rate of PCR+ cases for B. pertussis. Laboratory values may show leukopenia or lymphopenia in patients with pertussis. It is necessary to use appropriate laboratory diagnostic tests in all infants with respiratory symptoms for B. pertussis. Since, the clinical diagnosis overestimates the diagnosis of pertussis.